Fatigue in healthcare workers with mild COVID-19 survivors in Indonesia - Sinaga, Bintang YM.; Siagian, Parluhutan; Sinaga, Joshua P.; Samodra, Yoseph L. (Narra J, 2024)
Persistent symptoms after the coronavirus disease 2019 (COVID-19, known as post-COVID syndrome (PCS), presented an ongoing health burden among COVID-19 survivors, including health workers. The existence of fatigue in mild COVID-19 survivors has not been widely reported. The aim of this study was to present the symptoms of fatigue in healthcare workers who experienced mild COVID-19 and the factors associated with fatigue. A cross-sectional study was conducted at H. Adam Malik General Hospital in Medan, Indonesia, from September to December 2022, included doctors, nurses, ancillary workers, and medical support workers who experienced mild COVID-19. Fatigue was measured by a fatigue assessment scale (FAS). The assessed possible risk factors were gender, age, vaccination history, comorbid, presence of PCS, duration of PCS symptoms, and number of PCS symptoms. The chi-squared or Fisher’s exact test was used to assess the association between the incidence of fatigue and risk factors. A total of 100 healthcare workers of mild COVID-19 survivors were included. Most of them were nurses (58%), women (81%), and aged 19−30 years old (36%). The majority had incomplete vaccination history (64%), experienced PCS (71%), no comorbidities (61%), and experienced <3 months of PCS symptoms (55%). Mild to moderate fatigue was found in 23% of healthcare workers and only 1% experienced severe fatigue. No significant association was found between gender, vaccination history, and comorbidities with the incidence of fatigue. However, a significant association was observed between age (p=0.021), the presence of PCS (p=0.041), and the number of PCS symptoms (p=0.047) with fatigue incidence. Furthermore, there were significant associations between symptoms of PCS (confusion (p=0.004), insomnia (p=0.001), myalgia (p=0.035), arthralgia (p=0.028), throat pain (p=0.042), headache (p=0.042), and chest pain (p=0.011)) with fatigue. These findings can contribute to providing the necessary support for mild COVID-19 survivors and persistent fatigue.